Career Success, Participation and Representation of Women Academic Lecturers as Leaders in an Indonesian Tertiary Institution - Harahap, Hamida Syari; Yasya, Wichitra; Saimima, Ika Dewi Sartika (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
The role of women in academic and structural positions in tertiary institutions is an important part of achieving gender equality, particularly in the educational sphere. The purpose of this research is to investigate the perceptions of women lecturers’ career success, participation, and representation, and to determine the factors that impede them or serve as barriers for women’s career success, participation, and representation in tertiary institutions. The research used a mixed methods approach, namely quantitative surveys that were analyzed using descriptive statistics, while qualitative data and descriptive statistical results were used to carry out model gender analysis of Sara H. Longwee’s